Dampak Lingkungan terhadap Perkembangan Nilai Agama dan Moral Anak Usia Dini - Dwi Aminatus Sa'adah; Misbahul Huda; Desi Ismawati; Anikmah (Institut Agama Islam Nahdlatul Ulama Tuban, 2024)
This study describe the environmental impact on the development of religius anda moral values of children aged 4-5 years at Ihyaul Ulum Lamongan. This type of research is qualitative approach with a case study design. Data collection techniques using observation, interviews and documentation. Data were analyzed using the Miles and Hubberman technique through a process of reduction, display and verification. The results showed that the development of religious and moral values was not in accordance with the standard level of development achievement of children aged 4-5 years due to the environmental impact of children living like children imitating immoral scenes. Early age should be the age of the child in imitation of what he hears, sees, and feels.